Answered

Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

helppppp and explain pls and thankyouuu

Helppppp And Explain Pls And Thankyouuu class=

Sagot :

Answer:

third option (7.5, 8)

this option (6, 5, -3)

Step-by-step explanation:

you eliminate one variant by expressing it through the other(s) until you have one equation with one variable.

that you solve, and then you go back to the other elimination expressions to calculate the others.

2x - y = 7

-2x + 3y = 9

since the terms with x are already so similar, we could now simply add both equations and solve that result :

2x + (-2x) -y + 3y = 7+9 = 16

0×x + 2y = 16

2y = 16

y = 8

=>

2x - 8 = 7

2x = 15

x = 7.5

x - 2y - 3z = 5

x + 2y + 3z = 7

x + z = 3

the same trick by adding the first 2 equations

x + x -2y + 2y -3z + 3z = 5 + 7 = 12

2x + 0y + 0z = 12

2x = 12

x = 6

=>

6 + z = 3

z = -3

and then

6 + 2y + 3(-3) = 7

6 + 2y - 9 = 7

2y - 3 = 7

2y = 10

y = 5

We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.